A possible regulatory link between Twist 1 and PPARγ gene regulation in 3T3-L1 adipocytes. Issue 1 (December 2016) - Ren, Rui; Chen, Zhufeng; Zhao, Xia; Sun, Tao; Zhang, Yuchao; Chen, Jie; Lu, Sumei; Ma, Wanshan
Abstract Background Peroxisome proliferator-activated receptor γ (PPARγ) is a critical gene that regulates the function of adipocytes. Therefore, studies on the molecular regulation mechanism of PPARγ are important to understand the function of adipose tissue. Twist 1 is another important functional gene in adipose tissue, and hundreds of genes are regulated by Twist 1. The aim of this study was to investigate the regulation of Twist 1 and PPARγ expression in 3T3-L1 mature adipocytes. Methods We induced differentiation in 3T3-L1 preadipocytes and examined alterations in Twist 1 and PPARγ expression. We used the PPARγ agonist pioglitazone and the PPARγ antagonist T0070907 to investigate the effect of PPARγ on Twist 1 expression. In addition, we utilized retroviral interference and overexpression of Twist 1 to determine the effects of Twist 1 on PPARγ expression. Results The expression levels of Twist 1 and PPARγ were induced during differentiation in 3T3-L1 adipocytes. Application of either a PPARγ agonist (pioglitazone) or antagonist (T0070907) influenced Twist 1 expression, with up-regulation of Twist 1 under pioglitazone (1 μM, 24 h) and down-regulation of Twist 1 under T0070907 (100 μM, 24 h) exposure. Furthermore, the retroviral interference of Twist 1 decreased the protein and mRNA expression of PPARγ, while Twist 1 overexpression had the opposite effect. Conclusions There was a possible regulatory link between Twist 1 and PPARγ in 3T3-L1 mature adipocytes. This regulatory link enhanced the regulation of PPARγ and may be a functional mechanism of Twist 1 regulation of adipocyte physiology and pathology.